ANALISIS FRAMING PEMBERITAAN KASUS TEROR KEPALA BABI KEPADA JURNALIS TEMPO DI PORTAL BERITA ONLINE TEMPO.CO DAN DETIK.COM - Ade Leasfita; Adevy Vanie; Cut Meutia Annisa (Jurnal Netnografi Komunikasi, 2026)
This study discusses the analysis of framing in news reports on the online media Tempo.co and Detik.com, using the framing model theory of Zhongdang Pan and Gerald M. Kosicky. Framing in news reports can be seen in how journalists strategize in compiling, narrating, writing, and emphasizing facts. Through the framing analysis by Zhongdang Pan and Gerald M. Kosicky, a fact can be categorized through framing using four main structures: Syntax, Script, Thematic, and Rhetorical. This study was conducted to examine the framing of news coverage regarding the pig head terror case targeting Tempo journalists, as reported by the online media outlets Tempo.co and Detik.com. The purpose of this study is to understand how these media outlets framed the terror case. The research approach used is qualitative, employing the framing analysis method developed by Zhongdang Pan and Gerald M. Kosicky. The data used for this study is primary data obtained through non-participant observation techniques from the online news portals Tempo.co and Detik.com. The results of the study show that there are differences in the framing of news by the online media Tempo.co and Detik.com, particularly in the amount of news coverage, differences in perspective, and the use of visual elements or photos in the presentation of news. Keywords: Framing, Journalists, Pig Head, Terror